The length of the large intestine in children determined by computed tomography scan. Issue 7 (7th September 2017) - Mirjalili, S. Ali; Tarr, Gregory; Stringer, Mark D
Abstract : Little information is available on the length of the normal large intestine and its component parts in children. This information would be useful for procedures such as colonoscopy. The aim of this study was to investigate the length of the large intestine and its component parts in New Zealand children. Archival deidentified pediatric supine abdominopelvic computed tomography (CT) scans were retrospectively analyzed. After exclusion criteria, a total of 112 scans (57 males and 55 females) were included in the study and divided into three age groups: 0–2 years ( n  = 33), 4–6 years ( n  = 40), and 9–11 years of age ( n  = 39). The length of the large bowel increased from a mean of 52 cm in children aged <2 years to 73 cm at 4–6 years and 95 cm at 9–11 years. In all age groups, the transverse colon was the longest segment, contributing ∼30% of the total length of the large bowel. In comparison to total large bowel length, the mean proportional length of the rectum (9–12%), sigmoid colon (23–27%), descending colon (19–22%), transverse colon (27–32%), and ascending colon (14–17%) varied little between the three age groups. There were no significant differences between males and females in all age groups. The cecum was located in the right upper quadrant in 27% of children aged 0–2 years but in the right lower quadrant in all 9–11 year olds. These data provide useful information on the length of the large intestine and its component parts in living children, which are particularly relevant to pediatric colonoscopy and surgery. Clin. Anat. 30:887–893, 2017. © 2017 Wiley Periodicals, Inc.